The Impact Factor: Views and Evaluation - Bhatia, Ketki; Gandhi, D. N. (Journal of Information and Knowledge, 2014)
Librarians and information scientists have been evaluating journals for at least 75 years. The impact factor is a very useful tool for evaluation of journals, but it must be used discreetly. Considerations included the amount of review or other types of material published in a journal, variations between disciplines and item-by-item impact. The Impact factor has been used for years to evaluate journals quality. The appropriate use of the impact factor is to understand its limitations. Many factors contribute to the number of citations per paper, including the science~ the nature of the research; the style of communication; editorial policy; circulation and readership; citation bias; conformism; authors' tendency to cite their own work; and reference; self promotion. In addition to those already reported. a further limitation of this, the amount of circulation of information through web. The journals status with regard to coverage in the lSI database as well as the occurrence of a title change is also very important. Impact factor is not a perfect tool to measure the quality of article but there is nothing better and it has the advantage of already being in existence and is therefore, a good technique for scientific evaluation. Experience has shown that in each specialty the best journals are those in which it is most difficult to have an article accepted. and these are the journals that have.an impact factor. These journals existed long before the impact factor was devised. The use of impact factor as a measure of quality is wide spread for it fits well with the opinion, in each field of the best journals in each specialty.